Dynamism of capital structure: evidence from selected South East Asia countries panel data - Haron, Razali; Ibrahim, Khairunisah; Mat Nor, Fauzias; Ibrahim, Izani; Alias, Norazlan (2011)
This study contributes to the capital structure literature by exploring the dynamics of capital structure of firms in the South East Asia region, namely Malaysia, Thailand and Singapore based on a partial-adjustment framework during a period of 2000-2009. This study concludes that target capital structure does exist hence supports the dynamic trade off theory of capital structure for firms in the region and firms do adjust to their target with varying speed of adjustment subject to country. This study also finds evidences on Malaysia firms that the greater use of short-term debt in capital structure leads to higher speed of adjustment.